Dynamics and Robust Control of a New Realizable Chaotic Nonlinear Model. (16th January 2021) - Higazy, M.; Mahmoud, Emad E.; Khalil, E. M.; Abdel-Khalek, S.; Abo-Dahab, S. M.; Alotaibi, Hammad
Abstract : We present a new viable nonlinear chaotic paradigm. This paradigm has four nonlinear terms. The essential features of the new paradigm have been investigated. Our new system is confirmed to have chaotic behaviors by calculating its Lyapunov exponents. The relations of the system states are displayed by a suggested new signal flow graph (SFG). The proposed SFG is discussed via some graph theory tools, and some of its hidden features are calculated. In addition, the system is realized via constructing its electronic circuit which helps in the real applications. Also, a robust controller for the system is designed with the aid of a genetic algorithm.